Lila, wani, korban: karakter tokoh werkudara pada lakon wahyu eka bawana sebagai wahana pendidikan karakter dan nilai-nilai etika dasar bagi anak sekolah dasar - Kuncoro, Bimo; Wicaksono, Andi; Daryanto, Joko (Didaktika Dwija Indria, 2025)
This study aims to analyze and map the alternative character representation of Werkudara in the traditional Javanese puppet performance (pakeliran) titled Lakon Wahyu Eka Bawana, specifically focusing on its potential as a medium for character education and fundamental ethical values for primary school children. Werkudara, commonly known for his strength, is uniquely interpreted through three principles: Lila (sincere sacrifice/sincerity), Wani (moral courage/integrity), and Korban (collective self-sacrifice). Employing a qualitative approach with textual analysis and Malinowski's functional theory, the study finds that these three principles transcend mere narrative function. Functionally, Lila serves as a basis for fundamental ethics (honesty and humility), Wani as moral inspiration (integrity and responsibility), and Korban as a strengthener of social solidarity (mutual cooperation and social care). The value mapping demonstrates that Werkudara's character is highly relevant and can be integrated into the primary school curriculum as a concrete model rooted in local wisdom. The study concludes that traditional arts like wayang kulit are living and functional cultural media, effective in instilling noble values and preserving morality within the community.